The Effect of Work Process Automation, Warehouse Management System, And Experts on Company Operational Efficiency with Smart Warehousing Mediation in E-Commerce Warehouses in Jakarta - Halim, Lunario Rizal; Santosa, Wahyuningsih; Dewayana, Triwulandari Satitidjati (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
Technology, especially in the logistics industry, has experienced rapid development and offers various benefits such as increased efficiency, productivity, and cost reduction, as well as supporting corporate sustainability. This study aims to evaluate the effect of work process automation, warehouse management systems, and experts mediated by smart warehousing on operational efficiency in e-commerce warehouses in Jakarta. This study uses a quantitative method with data analysis through a t-test using SPSS version 27 for Windows. The results of the study indicate that work process automation has no significant effect on smart warehousing and operational efficiency. On the contrary, the warehouse management system has a significant effect on smart warehousing and operational efficiency, while experts have no significant effect on both variables. The effect of smart warehousing on operational efficiency is also significant. These findings indicate that warehouse management systems such as WMS, ERP, OMS, and inventory management systems have a significant positive impact on operational efficiency. However, the lack of readiness and understanding of employees towards technology can hinder the effectiveness of the implementation of work process automation.